2019
DOI: 10.32098/mltj.02.2018.15
|View full text |Cite
|
Sign up to set email alerts
|

The immediate effects of whole body vibration on cervical joint position sense in subjects with forward head posture

Abstract: Forward head posture (FHP) is considered to be one of the most common postural disorders in the spinal column. Recently studies have reported impaired proprioception to be one of the results of prolonged FHP. Studies have suggested that vibration stimulus is capable of improving joint proprioception. Thus the aim of this study was to investigate the effects of one session of whole body vibration (WBV) training in standing position on cervical joint position sense in individuals with FHP. Thirty (12 females and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Similarly, in our study, the balance and joint position sensing of cervical flexion, extension, left and right rotation, and left and right lateral flexion improved significantly after the treatment of WBVT for four weeks in both weight-bearing and non-weight-bearing positions for the upper and lower extremities in children of CP. Another study demonstrated that including WBVT with head and neck retraction exercise improved cervical joint position sense [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in our study, the balance and joint position sensing of cervical flexion, extension, left and right rotation, and left and right lateral flexion improved significantly after the treatment of WBVT for four weeks in both weight-bearing and non-weight-bearing positions for the upper and lower extremities in children of CP. Another study demonstrated that including WBVT with head and neck retraction exercise improved cervical joint position sense [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another intervention that reduces pain and improves CJPS in patients with neck pain is locally applied vibration [ 15 , 16 ]. Vibration can be applied locally on specific muscles or tendons or as whole-body vibration (WBV) [ 17 ]. Both types of vibration stimulate proprioceptors; for example, muscle spindles [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which vibration activates muscles is described as the “tonic vibration reflex” [ 19 , 22 ]. It is believed that the vibration stimuli excite the muscle spindles, which, in turn send signals to the spinal cord where the polysynaptic reflex system is activated, consequently causing muscle contractions [ 17 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research suggests that mechanical vibrations of low amplitudes and frequencies provide a safe and effective way to improve the neuromuscular system (1) and cause neuromuscular adaptations over a short time period without much effort (2). In the literature, vibrational intervention is also called biomechanical stimulation, biomechanical oscillation, vibration training, whole-body vibration, vibration therapy and focal vibration therapy (2)(3)(4)(5)(6)(7)(8). Initially, during a vibration intervention, a vibration device (actuator) was placed directly on the body part.…”
Section: Introductionmentioning
confidence: 99%